MARXISM AND SOCIOLOGY - Alfaro Vargas, Roy (2014)
Lefebvre presents, in this article, a reflection around Marxism and the definition that thesociology acquires in relation to the former. Also it briefly explains the dialectical method,insofar as it is the basis for the development of a sociology that permits to unify the roleof the social sciences in the comprehension of the totality (in this case, the French totality).In the same way, Lefebvre sets up an ensemble of links among the Sociology and theEthnography, the Political Economy, the Psychology and the Politics, so as to apprehendthe contradictions that characterizes the social reality and, thus, to establish a scientificsociology.